Takhrij Hadith the Obligation of Dutiful Children to Parents - Pratama, Faishal Dhia; Haqq, Muhammad Valiyyul (Journal of Takhrij Al-Hadith, 2022)
The purpose of this study is to discuss the hadith about filial piety to parents. This study uses a qualitative approach with descriptive-analytical method. The formal object of this research is the takhrij hadith within the scope of hadith science, while the material object is the hadith about filial piety to parents. The results and discussion of this study indicate that the Hadith of Imam Muslim History No. 123 concerning filial piety to parents with valid quality. This study concludes that the hadith is maqbul ma’mul bih as the basis of Islam in the teachings of the obligation to serve parents.